The growth of post-implantation rat embryos on a static culture medium - Nasser, L. (My University, 1982)
Rat embryos of the post-implantation stage are grown on a static culture medium, for the purpose of assessing growth and development over a 2 day period. The technique used is referred to as the petri-dish culture chamber method. This involves the culture of rat embryos on rat serum, in a controlled environment. Postimplantation embryos from the 6,5 to 8 day stage, and consisting simply of the 3 germ layers, showed a 60% survival rate in. vit/io after 2h hours and A8 hours respectively. After a full A8 hours in vitfio the embryos demonstrated well developed beating hearts, and a neural groove in the process of closing. The survival rate of embryos explanted at later stages was not as successful. The results compare favourably with the results of other workers, using the same method of culture. An advantage of the petri-dish culture chamber is that it allows for easy experimental access to the embryos at all times;a factor to be considered in any technique involving surgical intervention. Although more sophisticated methods have since superseded the static environment petri-dish technique, it is recommended here that this method should not be totally replaced by the more modern circulating culture medium technique.
A dissertation submitted to the Faculty of Dentistry, University of the Witwatersrand, Johannesburg, in part- fulfilment of the requirements for the Degree of Master of Science in Dentistry 1982
Keywords: Embryonic Development; Pem protein, rat; Surgical Procedures, Operative